2002
DOI: 10.1080/02687030244000220
|View full text |Cite
|
Sign up to set email alerts
|

English performance of proficient bilingual adults on the Boston Naming Test

Abstract: Background: The Boston Naming Test is widely used in several versions and languages. However, there are few studies of its use with bilingual adults. A recent study by Kohnert, Hernandez, and Bates (1998) found that Spanish/English bilingual adults scored well below unilingual adults. Aims: This study tested two hypotheses. (1) Fluently bilingual adults will obtain significantly lower scores than unilingual, English-speaking adults on the BNT, in English. (2) The order of difficulty of the 60 items will differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
116
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 24 publications
10
116
1
5
Order By: Relevance
“…Research with French Canadians suggests that the French translation of the BNT does not account for cultural appropriateness, which is important when administering the test in a language other than the one in which it was originally developed (Roberts & Doucet, 2011). Specifically, research suggests that the French translation of the BNT is not acceptable for assessing naming abilities in English-French bilinguals or in monolingual French individuals (Roberts & Doucet, 2011;Sheppard, Kousaie, Monetta, & Taler, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Research with French Canadians suggests that the French translation of the BNT does not account for cultural appropriateness, which is important when administering the test in a language other than the one in which it was originally developed (Roberts & Doucet, 2011). Specifically, research suggests that the French translation of the BNT is not acceptable for assessing naming abilities in English-French bilinguals or in monolingual French individuals (Roberts & Doucet, 2011;Sheppard, Kousaie, Monetta, & Taler, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, bilinguals have demonstrated difficulty with verbal fluency, frequent tip-of-thetongue states, and longer picture naming latencies (Bialystok, 2009), even when completing the task in their dominant language (Gollan & Acenas, 2004). Additional studies have indicated that bilinguals perform worse on naming tasks such as the BNT, both in measures of accuracy (Bialystok, Craik, & Luk, 2008;Kohnert, Hernandez, & Bates, 1998) and response time (Gollan et al, 2005;Gollan, Fennema-Notestine, Montoya, & Jernigan, 2007;Ivanova & Costa, 2008;Roberts et al, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations